Ischemia-modified albumin levels in patients with acute decompensated heart failure treated with dobutamine or levosimendan: IMA-HF study - Çavuşoğlu, Yüksel (Anatol J Cardiol, 2016)
OBJECTIVE: Ischemia-modified albumin (IMA) is a sensitive biomarker of myocardial ischemia. However, data on IMA levels in acute heart failure (HF) are still lacking. In this study, we aimed to evaluate serum IMA levels in acute decompensated HF and the effects of dobutamine and levosimendan treatments on IMA levels. METHODS: This was a prospective, multicenter study that included 70 patients hospitalized with acute decompensated HF and left ventricular ejection fraction <35%. Blood samples for IMA measurements were obtained on admission and 24-48 h after the initiation of HF therapy. Twenty-nine patients were treated with standard HF therapy, 18 received levosimendan, and 23 received dobutamine in addition to standard of care. A single serum specimen was also collected from 32 healthy individuals each. IMA concentrations were measured by the albumin cobalt binding colorimetric assay, and the results were given in absorbance units (AU). Independent and paired sample t-tests, Mann-Whitney U test, and Wilcoxon signed-rank test were used for the analysis. RESULTS: In patients with acute decompensated HF, the serum concentration of IMA was significantly higher than those of healthy subjects (0.894±0.23 AU vs. 0.379±0.08 AU, p<0.001). Overall, the IMA levels significantly decreased after 24-48 h of HF therapy (0.894±0.23 AU and 0.832±0.18 AU, p=0.013). Furthermore, the IMA levels were also found to significantly decrease with standard HF therapy (1.041±0.28 vs. 0.884±0.15 AU, p=0.041), with levosimendan (0.771±0.18 vs. 0.728±0.18 AU, p=0.046) and also with dobutamine (0.892±0.18 vs. 0.820±0.13 AU, p=0.035). CONCLUSION: Patients with acute decompensated HF had elevated IMA levels, and appropriate HF therapy significantly reduced the serum IMA levels. Dobutamine or levosimendan did not increase the IMA levels, suggesting a lower potential in inducing myocardial ischemia when used in recommended doses.